Biopsychosocial model of addictions and other approaches - Masiak, Jolanta (Polish Journal of Public Health, 2013)
Preparing the 5th Edition of Diagnostic Manual of Mental Disorders provokes the experts to express their opinions concerning the new classification of the psychiatric disorders. It takes into account also addictions. For some time the discussion concerning behavioral forms of addictions and their position in new revisions of both international classifications of mental disorders has taken place. The American Society of Addiction Medicine expressed the opinion concerning the new definition of addictions stressing relevance of biological mechanisms – mainly the brain reward, motivation, memory and related circuitry, and also genetic and envoirmental factors. The new definition of addictions is congruent with biopsychosocial model of addictions, which has revolutionized the DSM III. In this article the history and basic assumptions of biopsychosocial approach, and other theories that were precursors to this model are recalled.